Microarray Analysis of Suppression Subtracted Hybridisation Libraries Identifies Genes Associated with Breast Cancer Progression - Dong Liu Barraclough; Susan Sewart; Philip S. Rudland; Balvinder S. Shoker; D. Ross Sibson; Roger Barraclough; Michael P. A. Davies (Cellular Oncology)
Background: A major challenge of cancer research is to identify key molecules which are responsible for the development of the malignant metastatic phenotype, the major cause of cancer death.